Socioeconomic Status Drives Racial Disparities in HPV‐negative Head and Neck Cancer Outcomes. (10th November 2020) - Lenze, Nicholas R.; Farquhar, Douglas; Sheth, Siddharth; Zevallos, Jose P.; Blumberg, Jeffrey; Lumley, Catherine; Patel, Samip; Hackman, Trevor; Weissler, Mark C.; Yarbrough, Wendell G.; Zanation, Adam M.; Olshan, Andrew F.
Abstract : Objectives/Hypothesis: To determine drivers of the racial disparity in stage at diagnosis and overall survival (OS) between black and white patients with HPV‐negative head and neck squamous cell carcinoma (HNSCC). Study Design: Retrospective cohort study. Methods: Data were examined from of a population‐based HNSCC study in North Carolina. Multivariable logistic regression and Cox proportional hazards models were used to assess racial disparities in stage at diagnosis and OS with sequential adjustment sets. Results: A total of 340 black patients and 864 white patients diagnosed with HPV‐negative HNSCC were included. In the unadjusted model, black patients had increased odds of advanced T stage at diagnosis (OR 2.0; 95% CI [1.5–2.5]) and worse OS (HR 1.3, 95% CI 1.1–1.6) compared to white patients. After adjusting for age, sex, tumor site, tobacco use, and alcohol use, the racial disparity persisted for advanced T‐stage at diagnosis (OR 1.7; 95% CI [1.3–2.3]) and showed a non‐significant trend for worse OS (HR 1.1, 95% CI 0.9–1.3). After adding SES to the adjustment set, the association between race and stage at diagnosis was lost (OR: 1.0; 95% CI [0.8–1.5]). Further, black patients had slightly favorable OS compared to white patients (HR 0.8, 95% CI [0.6–1.0]; P = .024). Conclusions: SES has an important contribution to the racial disparity in stage at diagnosis and OS for HPV‐negative HNSCC. Low SES can serve as a target for interventions aimed at mitigating the racial disparities in head and neck cancer. Level of Evidence: 4 Laryngoscope, 131:1301–1309, 2021